Statin use in resected, high-risk cutaneous melanoma: A multi-centre retrospective cohort study - Charlie Yue Wang; Mark Shackleton; Sonia Mailer; Grant A. McArthur; Sophia Zoungas; Rory Wolfe; Victoria J. Mar (EJC Skin Cancer)
Background: Pre-clinical and clinical studies propose that statins may have chemopreventive effects against cancer, suggesting their possible roles as adjunctive therapies for melanoma. Objective: To investigate the association between regular statin use and disease recurrence in patients with resected Stage I-III melanoma. Methods: We conducted a retrospective analysis of patients enrolled in the multi-center Melanoma Research Victoria cohort with a histologically confirmed, resected American Joint Committee on Cancer Stage I-III cutaneous melanoma. Patients with uveal melanoma, melanoma of unknown primary site, or mucosal melanoma were excluded. Melanoma recurrence outcomes were compared between statin users and statin non-users, with statin use determined by linkage to the Pharmaceutical Benefits Scheme (Australia) prescription database. Results: 624 patients with resected Stage I-III melanoma at diagnosis were eligible for the study. 193 patients were classified as statin users and 431 patients as statin non-users. In all, 45 statin users experienced disease recurrence compared to 140 (23.3 vs 32.5%, p = 0.05) statin non-users with similar durations of follow-up (median 2.2 and 2.4 years, respectively). After adjustment, statin users had a lower risk melanoma recurrence than statin non-users (HR 0.66, 95%CI 0.44–0.99, p = 0.04). A lower risk of recurrence was also observed in subset analyzes of statin users on high-dose therapy (HR 0.50, 95%CI 0.25–0.99, p = 0.05) and patients who were adherent to statin therapy (HR 0.60, 95%CI 0.39–0.92, p = 0.02). Conclusion: Our study supports the possibility that an association exists between statin use and reduced disease recurrence in resected cutaneous melanoma.